Determination of The Suspect as A New Irrational Norm With The Paradigm of Presumption of Innocence - Sukardi Sukardi (VRISPRAAK : International Journal of Law, 2024)
The terms suspect, defendant and convict are the legal statuses of a person who is undergoing the process of criminal justice in the criminal justice system, which is automatically provided by law and is not determined, accordingly, procedurally there are no regulations regarding its determination in the Criminal Procedure Code and its implementing regulations. The new paradigm that includes "Determination of the suspect” as an object of a pre-trial shall be the manifestation of a new norm with the view of placing the status of a suspect as if it were the same as a convict, but it does not yet have a juridical basis in its application so that it is contrary to the principle of legality and can lead to multi-interpretations that is irrational with the understanding of the principle of the presumption of innocence. The understanding of the status of the suspect which is exclusively out of the context of interpretation as part of the presumption of innocence may result in norm conflicts between the application of new norm in determining suspects with the principle of legality which requires a legal basis in the first place, as well as the non-retroactive principle. The understanding of the principle of the presumption of innocence should continue to be socialized to build the society law culture, especially eliminating the negative stigma against the status of the suspect, not just justifying the negative stigma against the existence of the suspect as if interpreted like a convict. This negative stigma colors the society law culture in which results in low public participation in law enforcement to realize legal objectives.